2017
DOI: 10.1136/bmjopen-2016-014435
|View full text |Cite|
|
Sign up to set email alerts
|

Factors predicting self-reported medication low adherence in a large sample of adults in the US general population: a cross-sectional study

Abstract: ObjectivesThe study objective was to determine the level and correlates of self-reported medication low adherence in the US general population.SettingA 30 min cross-sectional online survey was conducted with a national sample of adults.Participants9202 adults (aged 18+) who had filled at least three or more prescriptions at a community pharmacy in the past 12 months.Primary and secondary outcome measuresSelf-reported medication adherence was measured with the 8-item Morisky Medication Adherence Scale.ResultsLo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…Our findings add to the body of literature that has identified a substantial number of factors associated with nonadherence, 2,23 while uniquely contributing understanding of inconveniences (or conveniences) in the management of medications in pharmacy and home contexts. Specifically, our findings indicate that the way that patients obtain their medications from a pharmacy, how they manage and organize their medications at home, including whether they are not satisfied with and bothered by medication management, are aspects that can affect the likelihood of adults taking medications as prescribed.…”
Section: Discussionsupporting
confidence: 53%
“…Our findings add to the body of literature that has identified a substantial number of factors associated with nonadherence, 2,23 while uniquely contributing understanding of inconveniences (or conveniences) in the management of medications in pharmacy and home contexts. Specifically, our findings indicate that the way that patients obtain their medications from a pharmacy, how they manage and organize their medications at home, including whether they are not satisfied with and bothered by medication management, are aspects that can affect the likelihood of adults taking medications as prescribed.…”
Section: Discussionsupporting
confidence: 53%
“…The nonadherence to treatment in our study is somewhat lower than that obtained in the meta-analysis conducted by Naderi et al (43% in patients with an average age of 64 years), and another study by Alves et al in which a prevalence of 50% was found in a population with multimorbidity and with a mean age of 56.5 years [34,35]. These differences can be explained by the age ranges included in each of the studies, where, as reported by Feehan et al, younger age is associated with lower levels of adherence [36].…”
Section: Strengths and Comparison With Other Studiesmentioning
confidence: 91%
“…It showed that up to 42% users are in this situation. Another purpose of this work was to correlate the non-adherence with other factors, such as being part of an ethnic minority, using multiple healthcare providers and experiencing barriers to access primary care, and this correlation was also confirmed (Feehan et al, 2017 ). In relation with chronic disorders, some works addressed the non-adherence among patients with diabetes using self-reporting and clinical data (Natarajan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 79%